2005
DOI: 10.1111/j.1365-313x.2005.02430.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant 7SL RNA genes belong to type 4 of RNA polymerase III‐ dependent genes that are composed of mixed promoters

Abstract: SummaryThe genes transcribed by RNA polymerase III (pol III) display a great diversity in terms of promoter structure and are placed in four groups accordingly. Type 3 subset of pol III genes has promoter elements which reside entirely upstream of the coding region of the gene whereas type 4 consists of genes with mixed promoters that enclose intra-and extragenic regulatory sequences. Plant 7SL RNA genes have been previously classified as type 3 of pol III genes requiring an upstream sequence element and a can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…By contrast, addition of tagetin (0.5 U/μl), a Pol III‐specific inhibitor, completely abolished transcription from all three templates. tRNA and 7SL RNA have previously been established as Pol III genes in Drosophila , human, and plants (Ullu and Weiner, 1985; Takada et al , 2000; Yukawa et al , 2005). Interestingly, snoRNAs have been reported to rely on either Pol II or Pol III for transcription (Antal et al , 2000; Kiss, 2002; Harismendy et al , 2003; Roberts et al , 2003; Moqtaderi and Struhl, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, addition of tagetin (0.5 U/μl), a Pol III‐specific inhibitor, completely abolished transcription from all three templates. tRNA and 7SL RNA have previously been established as Pol III genes in Drosophila , human, and plants (Ullu and Weiner, 1985; Takada et al , 2000; Yukawa et al , 2005). Interestingly, snoRNAs have been reported to rely on either Pol II or Pol III for transcription (Antal et al , 2000; Kiss, 2002; Harismendy et al , 2003; Roberts et al , 2003; Moqtaderi and Struhl, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of snoRNA:314 gene, it appears that significant gene‐external sequences and promoter elements may be necessary for transcriptional initiation as in vitro transcription experiments with promoter deletions of the snoRNA:314 template revealed that at least ∼250 bp upstream of the putative transcription start site are essential for efficient initiation. This suggests that the promoter structure of snoRNA:644 gene may resemble tRNAs whereas that of snoRNA:314 is more similar to the 7SL RNA gene in plants wherein both gene‐external and ‐internal sequence elements play a role in directing transcriptional initiation (Yukawa et al , 2005). Interestingly, under our in vitro transcription system, the snoRNA:644 template produced larger amounts of transcripts than the snoRNA:314 template.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids pAt7SL1, pAtU2.2, pAtU3CP, and pBAU6-28 include Arabidopsis 7SL RNA, U2 snRNA, U3 snoRNA, and U6 snRNA gene promoters, respectively Yukawa et al, 2005;Yukawa et al, 2013). Plasmids pNS10, pNtYI, and pGNPS include tobacco (Nicotiana tabacum) promoters from rbcS (Ntss23), tRNA Tyr , and b-1,3-glucanase genes, respectively (Mazur and Chui, 1985;Stange and Beier, 1986;Yukawa et al, 2001).…”
Section: Plasmids For In Vitro Transcription Assaysmentioning
confidence: 99%
“…to transcribe b-1, 3-glucanase gene, and light-harvesting chlorophyll a/bbinding protein (lhcb1) genes; Hasegawa et al, 2003b), and Pol III (e.g. to transcribe tRNA genes, U3 snoRNA genes, U6 snRNA gene, 7SL RNA genes, SINE retroposon, and 5S rRNA genes; Akama et al, 1998;Arnaud et al, 2001;Cloix et al, 2002;Hasegawa et al, 2003a;Mathieu et al, 2003;Yukawa et al, 2005;Dieci et al, 2006;Yukawa et al, 2011). However, the BY-2 cells are nonphotosynthetic.…”
mentioning
confidence: 99%
“…Specifically, AtR18 was not processed into a smaller fragment and no small open reading frames (sORFs) were included. Short interspersed elements (SINEs) and 7SL (signal recognition particle) RNA for protein trafficking are known as Pol III-derived RNA, with exception of the canonical functional RNA [73,74]. …”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%